Demand Driven DRP: Assessment of a New Approach to Distribution - Yassine Erraoui; Abdelkabir Charkaoui; Abdelwahed Echchatbi (International Journal of Supply and Operations Management, 2019)
The distribution of goods from suppliers to customers plays an important role in the supply chain. In this paper, the approach of Demand Driven Distribution Resource Planning (DDDRP) is proposed in order to optimize the distribution flow in the supply chain. The purpose is to manage all sources of variability "operational, management, supply and demand", while improving the traditional methods as Distribution Resource Planning (DRP). A literature review is presented about the impact of variability on distribution flow, and the solutions proposed in this context. Then, a general study of distribution industries is investigated in order to apply the DDDRP method; we show the buffer positioning in the distribution network, and the profile and levels for these buffers. After the dynamic adjustment, we present the Demand Driven Planning and the execution based on the net flow equation. The results discuss the approach and the steps of the implementation in the distribution industry.